Significance of Operative Legal Investigation as the Criterion of Reasonable Term Definition - V. A. Azarov; D. G. Rozhkov (Сибирское юридическое обозрение, 2013)
The article is devoted to the problem of tardiness of criminal procedure which can lead to breaches of human rights self-dependently.